PENGARUH KEMAMPUAN KOMUNIKASI INTERPERSONAL DAN EFIKASI DIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Yulianto, Agus; Mashudi, Mashudi; Herkulana, Herkulana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The aims of this research to examine and analyze the Effect of Interpersonal Communication Ability and Self-Efficacy on the Critical Thinking Ability of Class XI Students in Economic Subjects at SMAN 01 Sekadau. The method used is an associative quantitative research method with a form of causal relationship research. The population in this study were students of class XI IIS totaling 123 students, taken by simple random sample that is obtained 55 samples. Data analysis in this study used multiple linear regression analysis with the SPSS version 22.00. The results of the analysis revealed that there was a significant influence on interpersonal communication skills and self-efficacy on students' critical thinking skills, with a value of Fcount> Ftable (32.535> 3.18) and a probability value (sig) smaller than the significant degree (0,000 <0, 05). Then simultaneously the coefficient of determination (R Square) of 0.556, it can be stated that the coefficient of determination KD = R2 x 100% or KD = 0.556 x 100% = 55.6%. So interpersonal communication skills and self-efficacy have a close relationship with students' critical thinking skills of 55.6%. Keywords: Interpersonal Communication Ability, Self Efficacy, Ability Critical Thinking